SENSE AND SENSIBILITY - Austen, Jane, 1775-1817, author 199816 (London, England : Penguin Books Ltd., 1994)
Unfairly deprived of their family inheritance by the grasping Mrs John Dashwood and ker husband, Elinor and Marianne Dashwood and their mother find themselves in greatly reduced circumstances. Compelled to leave Norland in Sussex for Barton Cottage in Devonshire, the two sisters are soon accepted into their new society. Marianne, whose sweet radiance and open nature charm the roguish John Willoughby, is soon deeply in love. Elinor, whose disposition is more cautious and considered, who carefully conceals her emotions, is suffering the loss of Edward Ferrars whom she has left behind. Despite their very different personalities, both sisters experience great sorrows in their affairs of the heart: Marianne demonstrably wretched and Elinor allowing no one to see her private heartache. It is, however, the qualities common to the both - discernment, constancy and integrity in the face of the fecklessness of others - that allow them entry into a new life of peace and contentment.